2020
DOI: 10.1177/2041669520961116
|View full text |Cite
|
Sign up to set email alerts
|

In the Blink of an Eye: Reading Mental States From Briefly Presented Eye Regions

Abstract: Faces provide not only cues to an individual’s identity, age, gender, and ethnicity but also insight into their mental states. The aim was to investigate the temporal aspects of processing of facial expressions of complex mental states for very short presentation times ranging from 12.5 to 100 ms in a four-alternative forced choice paradigm based on Reading the Mind in the Eyes test. Results show that participants are able to recognise very subtle differences between facial expressions; performance is better t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 58 publications
2
17
0
2
Order By: Relevance
“…Despite this clear effect, the authors summarized their findings that children “may not be dramatically impaired by mask wearing during the COVID-19 pandemic” ( Ruba & Pollak, 2020 , p. 9), by focusing on the above-chance level performances and due to the fact that the participants were not less handicapped in reading emotions when face masks covered others’ faces than when covered by sunglasses. In the case of face masks, they concluded that the eye region is sufficient in dissolving the targeted emotions, which mirrors recent results from presenting eye regions only ( Schmidtmann et al., 2020 ). Nevertheless, the study by Ruba and Pollak (2020) is rather limited for making solid inferences on the recognition ability of emotions in masked faces per se because only three emotions were tested, and all of these emotions were negative emotions (sadness, anger, and fear).…”
supporting
confidence: 71%
See 1 more Smart Citation
“…Despite this clear effect, the authors summarized their findings that children “may not be dramatically impaired by mask wearing during the COVID-19 pandemic” ( Ruba & Pollak, 2020 , p. 9), by focusing on the above-chance level performances and due to the fact that the participants were not less handicapped in reading emotions when face masks covered others’ faces than when covered by sunglasses. In the case of face masks, they concluded that the eye region is sufficient in dissolving the targeted emotions, which mirrors recent results from presenting eye regions only ( Schmidtmann et al., 2020 ). Nevertheless, the study by Ruba and Pollak (2020) is rather limited for making solid inferences on the recognition ability of emotions in masked faces per se because only three emotions were tested, and all of these emotions were negative emotions (sadness, anger, and fear).…”
supporting
confidence: 71%
“…There are also results which support the view that covering parts of the mouth can lead to better performances in certain tasks. By blocking out irrelevant or deceptive information in faces, people can sometimes focus on the relevant eyes region resulting in better performance (Kret & de Gelder, 2012)-to focus on the eyes region is also beneficial if people have to detect deception (Leach et al, 2016) which supports the view that some mental states are already fully detectable when observing only the eyes (Schmidtmann et al, 2020). The literature about the impact of occlusions on the ability to read facial emotions is all in all quite contradictory.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, face masks can hamper the intelligibility of vocal messages (Cohn et al, 2021; Giovanelli et al, 2021). The gaze cueing effect addressed in the present study has been shown to imply the extraction of high-level information about the intentions of the interaction partner and therefore it represents one of the building blocks of social communication (e.g., Colombatto et al, 2020; see also Schmidtmann et al, 2020). The present data indicate that the attentional response to a nonverbal spatial cue conveyed by gaze direction can be observed irrespective of face mask, and hence suggest that this micro-level component of social interaction is preserved.…”
Section: Discussionmentioning
confidence: 80%
“…You will, most probably, experience the following: The people around you will appear somewhat strange to you—this mainly perceptual effect is based on an insufficient familiarity with the specific disguise. Furthermore, with such masks on, we cannot rely anymore on typical processes which we effortlessly use in normal, everyday life without any masks, for example, reading the emotional state ( Carbon, 2020 ) and further mental states ( Schmidtmann et al., 2020 ) of others by merely processing the holistic facial information. Yet, you will probably feel less strange about yourself as soon as you put on a mask as well—this effect traces back to the descriptive social norm that is established by the outward appearance (the shared dress code) of the majority of people around you in this specific situation.…”
Section: Discussionmentioning
confidence: 99%